Are smokeless tobacco products less harmful than smoking tobacco products?: A Review - Monika Srivastav; Thayalan Dinesh Kumar; Elizabeth C Dony (Wolters Kluwer Medknow Publications, 2022)
Background: The common belief amongst the consumers of smokeless tobacco products is Smokeless Tobacco Products (STPs) are not hazardous as smoking tobacco. Any form of tobacco consumed is addictive and the nicotine absorbed from these products is manifold higher than the nicotine produced and delivered from a cigarette. Aim: The aim of this narrative review is to consolidate and summarize the data from various studies to find out whether smokeless tobacco products are less harmful than smoking tobacco products or vice-versa. Method: A comprehensive literature search was conducted using various databases like EBSCO, Google scholar, Pubmed, Embase from 1957 to 2021. The keywords used for search was 'smokeless tobacco products', 'bacterial population AND smokeless tobacco products', 'water content, pH in STP'. Result: In total, 52 articles were selected to analyze the parameters, which proved increasing carcinogenicity in smokeless tobacco products. Various parameters were analyzed which include pH, water content, manufacturing procedure of STP and microbial population in smokeless tobacco products. Conclusion: The literature search suggests that the microbial population in smokeless tobacco products acts as a cascading series of events in carcinogenesis and other opportunistic infections and concludes that smokeless tobacco products are equally harmful as smoking tobacco products.